АНАЛІЗ ЕФЕКТИВНОСТІ ЕЛЕКТРОМЕХАНІЧНИХ СИСТЕМ ВІТРОЕНЕРГЕТИЧНИХ УСТАНОВОК З АЕРОДИНАМІЧНОЮ МУЛЬТИПЛІКАЦІЄЮ - Андрієнко, П.Д.; Алексієвський, Д.Г.; Близняков, О.В.; Немикіна, О.В.; Немудрий, І.Ю. (Інститут електродинаміки НАН України, Київ, 2023)
In this article, we have considered the state of development of high-power horizontal wind turbines. The most common wind turbines for operation with variable wind flow speed usually include a frequency converter to ensure the compatibility of generator with network. It leads to decrease in the efficiency of wind energy conversion system, while the use of direct connection of the generator to the axis of wind wheel leads to a significant increase in the weight and cost of the generator. The wind turbine with aerodynamic multiplication is an alternative to such systems. Its prototype with 750 kW power is manufactured and studied in Ukraine. This wind energy conversion system with the synchronous or induction generators offers the property to generate energy under optimal condition with invariable rotational speed of generator rotor within the wide range of variable speed of wind flow. In this case, it is not necessary to apply the frequency converter that contributes to increasing the efficiency and reducing the cost of wind turbine. As shown, the relative performances of mass, cost and efficiency of generators in proposed system comparatively to conventional one depend on the multiplication factor (i.e. ratio of the rotational speeds of wind turbine and generator). When the power of wind turbines is from 750 to 2500 kW, the multiplication factor is within the limits of 10.72 to 4.75. The theoretical and experimental study shows that the wind turbines with aerodynamic multiplication can be competitive as compared to conventional horizontal wind turbines. This article is aimed to comparative analysis of the quantitative and qualitative characteristics of the equipment used in high-power horizontal wind turbines with direct connection of generators to the axis of wind turbine and in wind turbines with aerodynamic multiplication. References 27, tables 1, figures 6.